Double Burden of Malnutrition: The Role of Framing in Development of Political Priority in the Context of Rising Diet-related Non-communicable Diseases in Tamil Nadu, India (P22-005-19). (13th June 2019) - Constantinides, Shilpa; Blake, Christine; Frongillo, Edward; Avula, Rasmi; Thow, Anne-Marie
Abstract: Objectives: In low- and middle-income countries, non-communicable disease (NCD) prevalence is increasing while undernutrition persists, resulting in a double-burden of malnutrition. How policy actors frame malnutrition may shape policy, programming, and investment. In India, where NCDs are rising rapidly and undernutrition persists throughout the country, much of food and health policy is decentralized, but little is known of how the double burden of malnutrition is understood at the state level. This study aimed to identify and compare frames and priorities for nutrition used by relevant policy actors to help understand the narrative emerging around policy solutions for the double burden of malnutrition. Methods: Key informants in the health, nutrition, and agriculture fields were identified from policy documents and purposive and snowball sampling. In-depth, semi-structured interviews were held with 28 key informants including international policy advocates, government officials, and state-level implementers in Tamil Nadu. Interviews were audio-recorded, transcribed, and coded with Nvivo 12. Major themes were identified using elements from prior published work: actor power, internal frame, issue characteristics, evaluative dimensions of target populations, priorities emphasized, and potential effects of the frame or likely policy result. Results: Different actors reported differing priorities for the double burden of malnutrition. There was almost universal concern about stunting and anemia in children and women and consensus on sanitation and dietary diversity as causes of undernutrition, but a lack of clarity regarding diet-related NCDs. Respondents were unclear about which populations to target for the double burden, compared to clear targeting of women and children to address undernutrition. They described lack of convergence or clear roles for actors addressing the double burden, unlike for undernutrition. Conclusions: There is a lack of consensus on the causes, manifestation, and solutions for the double burden of malnutrition within the policy community. Creating a shared narrative is critical for cohesive and efficient programming to address the double burden of malnutrition. Funding Sources: Bill & Melinda Gates Foundation through POSHAN, led by International Food Policy Research Institute.